Above ground utilities in Yakutsk, Russia ... - Campbell, Sandy (University of Alberta Library, 2014)
Because Yakutsk is on permafrost, utilities must be above ground. The city is heated by hot water boilers in several sectors. Hot water is carried through pipes like these to heat the city. ...